Implementasi Kebijakan Kredit Usaha Rakyat (KUR) di Bank Rakyat Indonesia Unit Tanjung Morawa Kabupaten Deli Serdang - Riri Novalina Peronica; Abdul Kadir; Indra Muda (Universitas Medan Area, 2022)
The role of banking in economic development is to channel funds for economic activities, one of which is in the form of credit for individual communities or business entities in the surrounding areas such as the Cape Morawa area. Bank Rayat Indonesia is an executing bank that distributes the most people's business loans. This is because Bank Rakyat Indonesia has a broad network compared to other implementing banks so that it is easy to distribute credit. So so so so that that aims to find out the implementation of policies and problems that occur in presenting Business Loans to customers at the Tanjung Morawa BRI Unit. This research method uses qualitative methods. Technique data through observation and documentation. By wrongly, the implementation of policies carried out by the Tanjung Morawa BRI Unit has not gone well, causing suspicion in the distribution of the People's Business Credit which is due to the communication made by the Bank and reducing existing human resources, resulting in reduced understanding of KUR for prospective customers.